EFFECT OF ADDED WATER DEPTH AND IRRIGATION INTERVAL ON SOME SOIL PHYSICAL PROPERTIES, GROWTH, AND YIELD OF WHEAT UNDER CENTER PIVOT SPRINKLER IRRIGATION SYSTEM WESTERN IRAQ - Sh. M. H. Al-mehmdy; M. J. A. Al-hashemi (مجلة الأنبار للعلوم الزراعية)
A field experiment was carried out during the winter season of 2021 in western Iraq to find out the effect of the depth-added water and the irrigation interval on some physical soil properties and the growth and productivity of wheat under the center pivot irrigation system (Valley). The study included two factors; the first factor is the water depth (d) with two levels, a complete water depth of 100% (df) and an overwater depth of 125% (do), while the second factor was the irrigation interval (I) with two levels of irrigation, every three days (I1) and irrigation every six days (I2), depending on soil texture and crop type. Wells water was used for irrigation. The results showed that the full water depth (df) achieved the best values of 1.380. MGm-3, 2.000 kg cm-2, 74.0 cm, and 4.367 ton ha-1 for the bulk density, soil resistance to penetration, plant height, and yield, respectively. The irrigation interval every three days (I1) achieved the lowest values of 1.37 MG m-3 and 1.875 kg cm-2 for both bulk density and soil penetration resistance, respectively, while it achieved the highest values of 76.938 cm and 4.436 tons ha-1 for both plant height and yield, respectively